Building the world's largest radio telescope: the Square Kilometre Array science data processor - Farnes, JS; Mort, B; Dulwich, F; Adamek, K; Brown, A; Novotny, J; Salvini, S; Armour, W; SKASDP Consortium (Institute of Electrical and Electronics Engineers, 2018)
The Square Kilometre Array (SKA) will be the largest radio telescope constructed to date and the largest Big Data project in the known Universe. The first phase of the project will generate 160 terabytes every second. This amounts to 5 zettabytes (5 million petabytes) of data that will be generated by the facility each year - a data rate equivalent to 5 times the estimated global internet traffic in 2015. These data need to be reduced and then continuously ingested by the SKA Science Data Processor (SDP). Within the SDP Consortium, we are contributing to various roles in the development of the telescope including building a lightweight end-to-end prototype of the major components of the SDP system - a project we call the SDP Integration Prototype (SIP). The aim is to build a mini, fully-operational SDP, for which we have been developing realistic SKA-like science pipelines that can handle these unprecedented data volumes.